BIOPHYSICAL MARKERS OF ISCHEMIC STROKE - V. Lychko (Eastern Ukrainian Medical Journal, 2020)
An important and influential factor that directly affects the severity of ischemic stroke (IS) and determines its outcome is the functional state of the membrane-receptor complex (MRC) of cells. One of the most important criteria for assessing this parameter is the β‑adrenergic activity of cytoplasmic membranes (β‑ARM), which plays a leading role in the pathogenesis of IS. The article presents the results of a comprehensive study of the peculiarities of changes in the structural and functional characteristics of brain tissue and β‑adrenoceptors in the acute period of IS to optimize diagnosis.Measurement of changes in the osmotic resistance of erythrocytes (ORE) under the action of β‑blockers was determined by photoelectron colorimetry.The work was based on the materials of a comprehensive examination of 350 patients with the new-onset IS on the 1st, 10th and 21st day of the disease. The severity of the condition and the degree of neurological deficit were objectified using the stroke scale of the National Institutes of Health (NIHSS) with a score in the first hours of the disease, in the dynamics of treatment on the 10th and 21st day.All patients were divided into 2 clinical groups: 1st (n = 183) – patients in moderate severity condition (mean score on the NIHSS scale 11.74 ± 0.33); 2nd (n = 167) – patients in severe condition (mean score on the NIHSS scale 24.06 ± 0.29).As a result of the study, the indicators of β‑ARM of the control group were within normal limits (15.3 ± 4.4 SU), which corresponds to normal β‑ARM. In patients with moderate IS, the indicator exceeded the control values by 1.97 times, which is typical for the average degree of β‑ARM (21–40 SU), and in severe – 2.8 times and was characterized by a low degree of β‑ARM (> 41 SU). An unfavorable sign for the prognosis of the acute period of IS was represented by a further increase in the levels of β‑ARM in the dynamics, which was observed in clinically severe patients.